Pengaruh Financial Technology Payment dan Self Control terhadap Perilaku Manajemen Keuangan Mahasiswa - Karunia Dwi Fadilatul Fatimah; Ellyawati, Noor; Rahayu, Vitria Puri (Educational Studies: Conference Series, 2024)
This research aims to determine whether fintech payment and self-control have a significant effect on the financial management behavior of students. The sampling technique used is proportional random sampling. Data collection carried out was observation and questionnaires distributed to 146 Economics Education Students of Mulawarman University. The data analysis technique used multiple linear regression analysis. The results of the partial t-test of each fintech payment and self-control variable have a positive and significant effect on financial management behavior, then the results of the F test significantly show that fintech payment and self-control have a positive and significant effect on financial management behavior. The R Square value is 68.0%, which means that the remaining 32.0% is influenced by other variables not examined in this study. And based on results t test analysis that has been done by the researcher obtained is partial influence and significant between Self control and Financial Management Behavior on student of Economics Education at Mulawarman University